Web 2.0 - Philippe Boistel (Communication)
With the expansion of Web 2.0, firms are increasingly solicited and sometimes indicted on the Web. The major consequence is the deterioration of the firm’s e-reputation, which is the reputation that emerges from all conversations on the Internet. Firms seek to maintain their e-reputation and to damper any and all consequences of such indictments on their share value, recruitment, and sales. Four French case studies serve to examine how e-reputations are echoed in the general media and what strategies firms adopt to maintain their e-reputation.